Labor Market Incorporation of Immigrants in Japan and the United States: A Comparative Analysis - Wayne A. Cornelius; Takeyuki Tsuda (Institute for the Study of Labor (IZA), 2002)
The most commonly used model of labor market incorporation among immigrants in the United States analyzes their earnings largely as a function of human capital variables such as education, language competence, age, length of residence and employment experience in the receiving country. However, such a simple model is not necessarily cross-culturally applicable and may lose much of its explanatory power in other societies, where immigrants encounter different labor market conditions. This paper estimates multivariate models of wage determination among samples of foreign workers interviewed in 1996 in San Diego County, California, and the Japanese industrial city of Hamamatsu. In contrast to San Diego, the standard measures of achieved human capital do not significantly influence immigrant wages in Hamamatsu. Instead, ascribed human capital (e.g., gender, ethnicity) has a much greater impact on immigrant wages in Japan than in the United States. Although the use of social networks by immigrants to find jobs has a significant impact on wages in both countries, the effect is positive in Hamamatsu, whereas it is negative in San Diego. The paper draws on data from ethnographic studies in Japan and California to suggest explanations for these divergent results. More generally, the paper illustrates the importance of reception contexts (host societies) in determining labor market outcomes for immigrant workers.
Keywords: J24; D63; J15; J61; J31; 330; wage determination; immigrants; labor brokerage; social networks; Migranten; Ausländische Arbeitskräfte; Arbeitsmarkt; Soziale Integration; Humankapital; Lohn; Soziales Netzwerk; Vergleich; Vereinigte Staaten; Japan